A Meta-Synthesis Study on Adaptation of Academic and Research Management during the COVID-19 Pandemic in Public Universities - Syahruddin Awg. Ahmad; Intan Soliha Ibrahim; Haslinda Hasan; Lai, Che Ching @ Abd Latif; Aisah Meri (Global Academic Excellence, 2022)
The ability of a tertiary institution to pursue academic studies and research during the pandemic and now endemic covid-19 is a measure of the strength of the university or college in facing the biggest test of this decade. Thus, various measures and approaches have been taken by the university management, especially in ensuring the momentum of study operations and even research at the university does not stop just like that. However, the biggest challenge seen and felt by all parties including students as the most important stakeholders is the online teaching and learning mechanism. Similarly, research planning and the ability of researchers are seen as very critical, especially in the success of data collection activities with the community and matters related to the study location. This meta-synthesis study potrayed the continuous efforts of the university in adapting and at the same time maintaining the quality of knowledge and skills taught are so significant and become the reason for the development of academic activities in crisis situations especially covid-19 pandemic. Studies from 2020 to 2021 were referred specifically to review teaching and learning situations as well as research during pandemics and endemics show that academics and researchers have an optimistic and dynamic attitude in adapting their respective teaching and research approaches.